Synthesis of Fungal Cell Wall Oligosaccharides and Their Ability to Trigger Plant Immune Responses. Issue 27 (15th July 2022) - Chaube, Manishkumar A.; Trattnig, Nino; Lee, Du‐Hwa; Belkhadir, Youssef; Pfrengle, Fabian
Abstract: Oligosaccharide fragments of fungal cell wall glycans are important molecular probes for studying both the biology of fungi and fungal infections of humans, animals, and plants. The fungal cell wall contains large amounts of various polysaccharides that are ligands for pattern recognition receptors (PRRs), eliciting an immune response upon recognition. Towards the establishment of a glycan array platform for the identification of new ligands of plant PRRs, tri‐, penta‐, and heptasaccharide fragments of different cell wall polysaccharides were prepared. Chito‐ and β‐(1→6)‐gluco‐oligosaccharides were synthesized by automated glycan assembly (AGA), and α‐(1→3)‐ and α‐(1→4)‐gluco‐oligosaccharides were synthesized in solution using a recently reported highly α‐selective glycosylation methodology. Incubation of plants with the synthesized oligosaccharides revealed i) length dependence for plant activation by chito‐oligosaccharides and ii) β‐1, 6‐glucan oligosaccharides as a new class of glycans capable of triggering plant activation. Abstract : Automated glycan assembly and solution‐phase synthesis provided a set of fungal cell wall oligosaccharides that were investigated for their ability to activate the plant immune system. Synthetic chitin and β‐1, 6‐glucan oligosaccharides triggered mitogen‐activated protein kinase phosphorylation and a reactive oxygen burst in Arabidopsis seedlings.